(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: IPAA is one of the most preferred procedures for ulcerative colitis. However, it is associated with many complications that can be early or late complications. These early complications are comparable to those seen in abdominal surgeries and seen in 30-50% of cases. Late complications are seen after more than 90 days post-surgery of IPAA. Aim: The present clinical study was conducted to evaluate the outcomes of IPPA and its designs on long-term functioning, neoplasia frequency in IPAA subjects, and IRA and IPAA outcomes in subjects having ulcerative colitis with concurrent PSC. Methods: In 186 subjects, demographics, medical history, general physical examination, diagnosis, surgery performed, functional outcomes, histopathology, associated complications, and failure. Pouch Functional Score, Endoscopy, Pouchitis, and Proctitis was recorded. Complications following IRA or IPAA were also evaluated. The collected data were subjected to statistical evaluation and the results were formulated. Results: With IPAA treatment, Bowel movement during daytime was scored as 0, 1, and 2 in 28.94% (n=11), 50% (n=19), and 15.78% (n=6) subjects respectively with UC and in 28.57% (n=2), 0, and 71.42% (n=5) subjects respectively with UC and PSC. Failure due to pouchitis was seen in 12.5% (n=2) of subjects having UC with PSC. More than 4 episodes of pouchitis were seen in 12.90% (n=4) subjects with UC alone and 62.5% (n=10) subjects having UC with PSC. Subjects having pouchitis were 32.25% (n=10) having UC alone and 81.25% (n=13) having UC with PSC. In IPAA, the subjects with UC with PSC and UC alone had 15% and 5% failure respectively which was statistically non-significant. However, in subjects treated with IRA, failure in subjects with UC alone and UC with PSC was 21% and 52% respectively. Conclusion: The present study concludes that the best long-term functional outcomes were seen in K-pouch with stapled anastomosing in subjects with ulcerative colitis with a very low incidence of neoplasia following treatment. High failure rates and compromised functional outcomes are seen in subjects having UC and PSC treated with IRA. However, IPAA showed comparable outcomes in subjects having UC only or UC with PSC